KINEMATIC SCHEME AND DYNAMIC MODEL OF THE NEWLY DESIGNED MULTICYCLONE DEVICE - Sherzod Sobirjonovich, Djurayev; Nosir Yusupjanovich, Haribayev (PT. Antis International Publisher, 2025)
Objective: This study aims to design and analyze a newly developed multicyclone device for improved impurity removal in cotton processing systems. Method: The design incorporates advanced kinematic schemes, and dynamic modeling is carried out by deriving the equations of motion using Lagrange's Second Equation to optimize performance. Results: The results show that the optimized multicyclone device significantly reduces rotational irregularities, minimizing fiber damage and enhancing impurity extraction efficiency. Novelty: This research offers a novel approach to cotton cleaning by integrating advanced dynamic modeling, which enhances the overall performance and efficiency of cotton processing systems, addressing key challenges in the industry.